Transcatheter management of post-surgical superior vena cava obstruction (Indian Journal of Case Reports, 2024)
Obstruction of the superior vena cava (SVC) is a rare complication after cardiac surgery in infants and children. We present the case of a 2-year-old male child who underwent surgery to repair a mixed total anomalous pulmonary venous connection. After 18 months of surgery, the child developed SVC syndrome. Transcatheter stenting was performed to relieve the SVC obstruction detected with transthoracic echocardiography. The patient was discharged after 5 days of hospitalization. The patient was doing well at follow-up appointments, with good laminar flow through the stent. In conclusion, transcatheter management of post-surgical complications of SVC obstruction was successful in this patient.